Protein Structure-Function Relationship at Work: Learning from Myopathy Mutations of the Slow Skeletal Muscle Isoform of Troponin T - Mondal, Anupom; Jin, J.-P. (Frontiers in Physiology, 2016)
Troponin T (TnT) is the sarcomeric thin filament anchoring subunit of the troponin complex in striated muscles. A nonsense mutation in exon 11 of the slow skeletal muscle isoform of TnT (ssTnT) gene (TNNT1) was found in the Amish populations in Pennsylvania and Ohio. This single nucleotide substitution causes a truncation of the ssTnT protein at Glu180 and the loss of the C-terminal tropomyosin (Tm)-binding site 2. As a consequence, it abolishes the myofilament integration of ssTnT and the loss of function causes an autosomal recessive nemaline myopathy (NM). More TNNT1 mutations have recently been reported in non-Amish ethnic groups with similar recessive NM phenotypes. A nonsense mutation in exon 9 truncates ssTnT at Ser108, deleting Tm-binding site 2 and a part of the middle region Tm-binding site 1. Two splicing site mutations result in truncation of ssTnT at Leu203 or deletion of the exon 14-encoded C-terminal end segment. Another splicing mutation causes an internal deletion of the 39 amino acids encoded by exon 8, partially damaging Tm-binding site 1. The three splicing mutations of TNNT1 all preserve the high affinity Tm-binding site 2 but still present recessive NM phenotypes. The molecular mechanisms for these mutations to cause myopathy provide interesting models to study and understand the structure-function relationship of TnT. This focused review summarizes the current knowledge of TnT isoform regulation, structure-function relationship of TnT and how various ssTnT mutations cause recessive NM, in order to promote in depth studies for further understanding the pathogenesis and pathophysiology of TNNT1 myopathies toward the development of effective treatments.□